2003
DOI: 10.1117/12.483762
|View full text |Cite
|
Sign up to set email alerts
|

<title>Modelling of smart fluid dampers</title>

Abstract: Smart fluid dampers offer an attractive solution to vibration damping problems where there is a need for variable damping behaviour. In recent years there has been a great deal of research effort in developing these dampers, and implementing appropriate control strategies. Consequently a wide range of modelling techniques have been proposed, for both device design and controller design processes. In general, however, the development of modelling and control techniques has proceeded in parallel to the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…In these studies, the rheological behaviors of the fluids suggested application of the solid models such as three-parameter model to represent the storage and loss moduli. Sims and Wereley (2003) employed the Maxwell fluid model to characterize an ER fluid in the pre-yield regime. In the Maxwell model, the loss and storage moduli approach 0 in small values of the excitation frequency, while in practice the pre-yield region is an elastic region and stiffness never fades out.…”
Section: Pre-yield Characterization Of Mr/er Fluidsmentioning
confidence: 99%
“…In these studies, the rheological behaviors of the fluids suggested application of the solid models such as three-parameter model to represent the storage and loss moduli. Sims and Wereley (2003) employed the Maxwell fluid model to characterize an ER fluid in the pre-yield regime. In the Maxwell model, the loss and storage moduli approach 0 in small values of the excitation frequency, while in practice the pre-yield region is an elastic region and stiffness never fades out.…”
Section: Pre-yield Characterization Of Mr/er Fluidsmentioning
confidence: 99%
“…Classification of the viscoelastic models is done according to fluid-like or solid-like behavior of the viscoelastic material. The common fluid-like viscoelastic models are viscous dashpot [4,5], Maxwell fluid [6,7], and threeparameter fluid [8,9]. Elastic spring [10,11], Kelvin-Voigt solid [12][13][14], and three-parameter solid [15] are the common solid-like viscoelastic models.…”
Section: Introductionmentioning
confidence: 99%
“…Viscoelastic models have commonly been used to represent the key rheological properties of the ERFs in the pre-yield regime [60][61][62]. These include solid-like models such as the Zener element model [63], Kelvin-Voigt model [64,65], the three parameter fluid models [66], and Maxwell fluid-like models [67,68].…”
Section: Electrorheological Fluid Modelmentioning
confidence: 99%